2022
DOI: 10.3390/agriculture12101538
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Community Driven by Soil Moisture and Nitrogen in Milk Vetch (Astragalus sinicus L.)–Rapeseed (Brassica napus L.) Intercropping

Abstract: The soil microbial community is not only driven by plant composition but is also disturbed by the soil environment. Intercropping affects the soil microenvironment through plant interaction, but the understanding of the relationship between soil microbial community and environment in intercropping is still weak. In this study, milk vetch intercropping with rapeseed was used to explore the interaction between soil microorganisms and environment. The results showed that the soil moisture content of intercropping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…We measured soil physiochemical variables. Soil moisture was determined by oven-drying, soil pH with a pH electrode, total organic carbon (TOC) with potassium dichromate oxidation, total nitrogen (TN) with the Kjeldahl method, total phosphorus (TP) with NaOH melting molybdenum antimony anti-colorimetry, total potassium (TK) with NaOH melting flame photometer, soil available nitrogen (AN) with the alkaline hydrolysis diffusion method, soil available phosphorus (AP) with sodium bicarbonate extraction, soil available potassium (AK) with ammonium acetate extraction and flame photometry, and soil aggregates with wet-sieving ( Bao, 2000 ; Du et al, 2015 ; Zeng et al, 2018 ; Tian et al, 2019 ; Liu Z. et al, 2022 ). Soil microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) were determined by the chloroform-fumigation extraction method ( Vance et al, 1987 ).…”
Section: Methodsmentioning
confidence: 99%
“…We measured soil physiochemical variables. Soil moisture was determined by oven-drying, soil pH with a pH electrode, total organic carbon (TOC) with potassium dichromate oxidation, total nitrogen (TN) with the Kjeldahl method, total phosphorus (TP) with NaOH melting molybdenum antimony anti-colorimetry, total potassium (TK) with NaOH melting flame photometer, soil available nitrogen (AN) with the alkaline hydrolysis diffusion method, soil available phosphorus (AP) with sodium bicarbonate extraction, soil available potassium (AK) with ammonium acetate extraction and flame photometry, and soil aggregates with wet-sieving ( Bao, 2000 ; Du et al, 2015 ; Zeng et al, 2018 ; Tian et al, 2019 ; Liu Z. et al, 2022 ). Soil microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) were determined by the chloroform-fumigation extraction method ( Vance et al, 1987 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, WC was the driver for the SD‐M0, SD‐M1, and BC‐M0, which suggested that microbial module community and function was related to soil moisture. Straw return can enhance soil water content and water retention, and then influence the substrates and energy substances available to soil microorganisms, finally improving their growth and activities (Hagemann et al, 2017; Liu, Li, et al, 2022; Siedt et al, 2021). In addition, BD was the only shared driver for the BC‐M1 and BC‐M3 but not for SD modules.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed cultivation, which creates structural heterogeneity may therefore be particularly beneficial for these vulnerable groups, with additional benefits from the limited use of agrochemicals associated with milk vetch cultivation. Considering the wide distribution of this crop mix in China (Liu et al., 2022) and other Asian countries (Sakai & Matsuka, 1982), understanding the potential benefits of mixed cultivation practices involving milk vetch for wild pollinator diversity and its potential to mitigate the negative impacts of ongoing agricultural intensification (Shi et al., 2021; Shi, Axmacher, et al., 2022) is a high priority.…”
Section: Introductionmentioning
confidence: 99%